(untitled) (Journal of Business Management and Accounting, 2024)
In this study, the level of financial literacy of university students from Kumasi Technical University was analysed. The aim of the research was to examine the financial literacy and saving behaviour of tertiary students using Kumasi Technical University as a case study. An online survey tool was used to collect the data. A sample size of 377 was drawn from the population by the convenience sampling method with data from primary sources. The quantitative data was analysed through descriptive statistics. Statistical Packages for Social Science (SPSS version 20) was employed to analyse the data. It was found out that the financial literacy among the respondents was average, especially among students studying business and management courses. This could be due to the fact that most of their courses of study are finance-related as compared to other students in other programmes. It was also found that the majority of respondents across different age groups felt that seeking financial information and advice had an impact on their decisions. However, a significant percentage (13.5 percent) of respondents aged 18 to 24 said that even if they had sought financial information and advice, their decisions had not been impacted. This study will provide guidance to policymakers and other regulators on how to develop appropriate strategies to increase savings among young people.